Lócus de controle materno, saúde bucal positiva e Hipomineralização Molar-Incisivo (HMI): uma investigação transversal - Letícia Cristine da Silva (2024)
Hypomineralization of Molar-Incisor (MIH) is a multifactorial enamel alteration affecting one or more first permanent molars, possibly associated with permanent incisors. This condition generates numerous consequences for individuals, such as sensitivity, increased risk for caries and fractures, as well as aesthetic problems. Investigating perceptions about this condition, especially maternal perception, is of paramount importance, considering that such a construct is one of the decisive factors regarding oral health care. Therefore, the present study aimed to investigate and compare the Locus of Control (LoC) and positive oral health of mothers of children with and without HMI. A comparative cross-sectional study was conducted with 111 children with and without HMI aged 6 to 12 years attended by different clinical of the Department of Child and Adolescent Oral Health (SCA) of the School of Dentistry at the Federal University of Minas Gerais (FAO-UFMG), and their mothers who answered socioeconomic, medical history, Brazilian - Positive Oral Health and Well-Being (B-POHW) instrument, and Locus of Control (LoC) questionnaires. Additionally, the children were clinically evaluated by a previously calibrated researcher for dental caries and HMI. Variables were analyzed descriptively, including absolute values and frequencies. Inferential tests of association and bivariate analyses were used (Pearson's Chi-Square, Linear Trend Chi-Square, and Mann-Whitney) to investigate the relationship between exposure variables and the investigated outcomes. Unadjusted and adjusted analyses were performed using Poisson Regression (Prevalence Ratio measure of association). Independent variables with p < 0.25 in the crude model were inserted into the adjusted model. The significance level adopted was 5%, with a 95% confidence interval, and the Statistical Package for Social Sciences (SPSS) program (25.0) was used. It was concluded that the predominant locus of control of mothers of children with HMI was internal locus of control, as well as a less positive self-perception regarding their own oral health, compared to mothers of children without HMI. The multivariate analysis also showed that first permanent molars with dental caries and mothers with oral health are more likely to have children with Molar-Incisor Hypomineralization